The Influence of Ethical Leadership on the Quality of Earnings Management in Multinational Corporations - Sri Kawuri; Gema Ika Sari (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
The study investigates the influence of ethical leadership on the quality of earnings management in multinational corporations (MNCs), a topic of significant interest in the fields of corporate governance, accounting, and organizational behavior. Earnings management, which refers to the manipulation of financial statements to meet certain objectives, is often viewed with skepticism due to its potential to obscure the true financial health of an organization. The ethical orientation of leadership plays a critical role in shaping corporate culture and decision-making processes, and thus may have a substantial impact on the practices of earnings management. This research employs a mixed-method approach, combining quantitative analysis of financial data from a sample of MNCs across different sectors and qualitative interviews with senior executives in these organizations. The findings indicate that ethical leadership, characterized by transparency, integrity, and a commitment to long-term stakeholder interests, is negatively correlated with aggressive earnings management practices. Organizations led by ethically driven leaders are more likely to adopt conservative accounting practices, leading to a higher quality of earnings that reflects the true performance of the company. Conversely, MNCs with less ethical leadership were found to be more prone to manipulating earnings to meet short-term targets or expectations from investors. Furthermore, the study highlights the role of organizational culture in mediating the relationship between ethical leadership and earnings management. Leaders who emphasize ethical standards foster a culture of accountability and transparency, which discourages manipulative financial reporting practices. The research also identifies that the impact of ethical leadership on earnings management varies depending on the corporate governance mechanisms in place, such as audit committees and regulatory compliance. The findings of this study contribute to the growing body of literature on corporate ethics and earnings quality, offering practical implications for policymakers, investors, and managers. By emphasizing the importance of ethical leadership, the research advocates for the integration of ethical guidelines into leadership development programs within multinational corporations. Additionally, the study suggests that fostering a strong ethical framework in MNCs can mitigate the risks of earnings manipulation, thus enhancing the credibility and sustainability of financial reporting. This research also opens avenues for further investigation into the mechanisms through which ethical leadership influences other aspects of corporate governance, such as risk management and corporate social responsibility. Ultimately, the study underscores the critical role that ethical leadership plays in promoting transparency and long-term value creation in the global corporate environment.